Influence of the Sex of Translocation Carrier on Clinical Outcomes of Couples Undergoing Preimplantation Genetic Testing - Zhiping Zhang; Jiayao Chen; Lei Zhang; Ruiyang Wei; Zhen Liu; Dunmei Zhao; Xingyu Bi; Lixia Liang; Xueluo Zhang; Dan Su; Xueqing Wu (Molecular Genetics & Genomic Medicine)
ABSTRACT Introduction This study investigated the impact of the carrier on transferable blastocyst rate and live birth outcomes in couples with structural chromosomal abnormalities. Methods Couples were grouped into reciprocal translocation, Robertsonian translocation, or inversions groups, and clinical data were retrospectively analyzed. Preimplantation genetic testing for chromosomal structural rearrangements (PGT‐SR) was conducted, and pregnancy outcomes were compared. Results Embryo euploidy rates between male and female carriers differed nonsignificantly in the reciprocal translocation and inversion groups but significantly among the three groups. In the Robertsonian translocation group, male carriers had a higher embryo euploidy rate than that of female carriers. Sperm density of male carriers with reciprocal and Robertsonian translocation was significantly lower than that of the female carrier in the same group, whereas the difference was non‐significant in the inversion group. The clinical outcomes of embryo transfer post‐PGT were similar regardless of the sex of carriers with structural chromosomal abnormalities. Female carriers with Robertsonian translocations displayed a higher risk of producing embryos with chromosomal abnormalities than male carriers. Pregnancy, live birth, and cumulative live birth rates following a PGT‐SR cycle were similar, irrespective of chromosomal structural rearrangement type, and carrier sex. Conclusion Our findings offer valuable information for genetic counseling.